Leucaena leucocephala introduction into a tropical pasture in the Chaco region of Argentina. Effects on soil carbon and total nitrogen = Introducción de Leucaena leucocephala en una pastura tropical en el Chaco argentino. Efectos en el carbono y nitrógeno total del suelo - Banegas, Natalia Romina; Corbella, Roberto; Viruel, Emilce; Plasencia, Adriana; Roig, Belen; Radrizzani Bonadeo, Alejandro (CIAT, 2020)
The introduction of leucaena (Leucaena leucocephala), apart from increasing animal production, improves soil fertility through biological nitrogen (N) fixation and its deep-rooted system. There is limited information on carbon and N dynamics in hedgerow silvopastoral systems, particularly in the subsoil profile. The concentrations and vertical distribution of organic carbon (OC) and total N , and their fractions (particulate and associate forms) in the profile (0‒100 cm) of a 4-year-old leucaena stand in a Urochloa brizantha-Chloris gayana pasture were compared with those in the adjacent pure tropical grass (U. brizantha) pasture. Leucaena introduction increased the OC concentration in the subsoil (20‒100 cm) by 45%, particularly the stable form (associate OC) in the deepest horizon (50‒100 cm). This was attributed to a greater abundance of leucaena roots deeper in the profile than for grass. Leucaena also enhanced by 7.6% the N concentration (from 0.131 to 0.141%) in the topsoil (0‒20 cm) associated with an increment in the labile form (particulate organic N), due to leaf deposition, recycling of animal feces and nodule-N turnover from N fixation. Leucaena establishment has the potential to improve soil fertility and hence availability of N to companion grass growth, and can be utilized as a greenhouse gas mitigation strategy.